Development policy and administration / edited by Kuldeep Mathur - "Mathur, Kuldeep P. (ed.)" (New Delhi, 1996)
This reader, the first in a new series, brings together essays which combine policy perspectives with analyses of the implementation of various development programmes in India. The chapters provide an understanding of the merging concerns in Indian public administration. Topics covered include: macro perspectives on the state and development planning; bureaucracy; the policy apparatus; and the role of international agencies, panchayats, cooperatives and NGOs in meeting the needs of the people.
Keywords: India economic policy 1980